Serotype-conversion in Shigella flexneri: identification of a novel bacteriophage, Sf101, from a serotype 7a strain - Jakhetia, Richa (BioMed Central, 2014)
BACKGROUND: Shigella flexneri is the major cause of bacillary dysentery in the developing countries. The lipopolysaccharide (LPS) O-antigen of S. flexneri plays an important role in its pathogenesis and also divides S. flexneri into 19 serotypes. All the serotypes with an exception for serotype 6 share a common O-antigen backbone comprising of N-acetylglucosamine and three rhamnose residues. Different serotypes result from modification of the basic backbone conferred by phage-encoded glucosyltransferase and/or acetyltransferase genes, or plasmid-encoded phosphoethanolamine transferase. Recently, a new site for O-acetylation at positions 3 and 4 of Rha(III), in serotypes 1a, 1b, 2a, 5a and Y was shown to be mediated by the oacB gene. Additionally, this gene was shown to be carried by a transposon-like structure inserted upstream of the adrA region on the chromosome. RESULTS: In this study, a novel bacteriophage Sf101, encoding the oacB gene was isolated and characterised from a serotype 7a strain. The complete sequence of its 38,742 bp genome encoding 66 open reading frames (orfs) was determined. Comparative analysis revealed that phage Sf101 has a mosaic genome, and most of its proteins were >90% identical to the proteins from 12 previously characterised lambdoid phages. In addition, the organisation of Sf101 genes was found to be highly similar to bacteriophage Sf6. Analysis of the Sf101 OacB identified two amino acid substitutions in the protein; however, results obtained by NMR spectroscopy confirmed that Sf101-OacB was functional. Inspection of the chromosomal integration site of Sf101 phage revealed that this phage integrates in the sbcB locus, thus unveiling a new site for integration of serotype-converting phages of S. flexneri, and determining an alternative location of oacB gene in the chromosome. Furthermore, this study identified oacB gene in several serotype 7a isolates from various regions providing evidence of O-acetyl modification in serotype 7a. CONCLUSIONS: This is the first report on the isolation of bacteriophage Sf101 which contains the S. flexneri O-antigen modification gene oacB. Sf101 has a highly mosaic genome and was found to integrate in the sbcB locus. These findings contribute an advance in our current knowledge of serotype converting phages of S. flexneri. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-742) contains supplementary material, which is available to authorized users.